Salivary biomarkers in psychoneuroimmunology. (August 2019) - Engeland, Christopher G; Bosch, Jos A; Rohleder, Nicolas
Highlights: Salivary cortisol and amylase have advanced the understanding of stress biology. Salivary inflammation appears to reliably increase following stress. Salivary S-IgA may provide a good general overview of the secretory immune system. Saliva may give unique insights into the effects of stress on health in PNI. Abstract : As molecular biology advances, an increasing number of proteins are becoming detectable at very low levels in different biological tissues. In this regard, saliva holds vast promise. Unlike blood, saliva can be sampled 1) non-invasively; 2) across all ages (newborn to elderly); 3) in the field; 4) by study participants; and 5) many times per day. With respect to psychoneuroimmunology (PNI), physiological measures of stress such as cortisol have been well characterized. Alpha amylase provides another physiological index of stress; it is a measure of autonomic nervous system activation and is quantifiable in saliva. Other salivary measures, such as inflammatory biomarkers and immunoglobulin A (IgA), provide valuable information pertaining to the effects of stress on inflammation, mucosal immunity, and oral health. Importantly, due to various methodological issues and a lack of strong correlation between saliva and blood measures, investigators should proceed with caution in drawing conclusions from measures of salivary inflammation that pertain to systemic immunity or generalized health.